Education on Packaging and Labeling for Milky Orange Powder Drink Products in Mundurejo Village, Jember Regency - Wiyono, Andi Eko; Mahardika, Nidya Shara; Sari, Vina Juanita; Tiwakana, Yolanda Maulani; Nashiruddin, Muhammad Luthfi; Leemans, Joshep Yoshio; Larasati, Misty Ayu; Prajamukti, Randhiagus; Pamungkas, Ari Candra Juni; Putra, Sigit Arya (PT FORMOSA CENDEKIA GLOBAL, 2024)
Mundurejo Village is one of the production centers for quality Siamese oranges in the Jember Regency. The problem often faced by Siamese orange farmers in Mundurejo Village is that the high production costs are not commensurate with the selling price of oranges, which falls in certain seasons due to intense market competition. Community service activities are carried out to improve residents' skills in processing oranges into products with high-selling value and better packaging and labels. The Service Team provides socialization and training on the production and packaging of milk orange powder drink products with an agenda of activities (1) Introduction to tools and technology in making and packaging products, (2) Socialization of the importance of packaging and labels on products, and (3) Product packaging and labeling practices. The Service Team succeeded in increasing the understanding and skills of the Mundurejo Village community regarding the importance of packaging and labels to maintain product quality and provide clear product information to consumers. It is hoped this activity will produce attractive and informative packaging so that the processed milky orange powder drink product can become a village icon and have a sustainable positive impact on the community.